2017
DOI: 10.1038/srep44133
|View full text |Cite
|
Sign up to set email alerts
|

A potential regulatory network underlying distinct fate commitment of myogenic and adipogenic cells in skeletal muscle

Abstract: Mechanism controlling myo-adipogenic balance in skeletal muscle is of great significance for human skeletal muscle dysfunction and myopathies as well as livestock meat quality. In the present study, two cell subpopulations with particular potency of adipogenic or myogenic differentiation were isolated from neonatal porcine longissimus dorsi using the preplate method to detect mechanisms underlying distinct fate commitment of myogenic and adipogenic cells in skeletal muscle. Both cells share a common surface ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 54 publications
4
33
0
Order By: Relevance
“…Ca 2+ , serving as the second messenger, regulates numerous cellular processes at the center of cell signaling [54] and has been shown to participate in the regulation of myogenic differentiation [35,55]. In this study, Ca 2+ concentration in both cytoplasmic and endoplasmic reticulum was lower in Myo-lineage cells of lean-type pigs relative to obese-type pigs.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Ca 2+ , serving as the second messenger, regulates numerous cellular processes at the center of cell signaling [54] and has been shown to participate in the regulation of myogenic differentiation [35,55]. In this study, Ca 2+ concentration in both cytoplasmic and endoplasmic reticulum was lower in Myo-lineage cells of lean-type pigs relative to obese-type pigs.…”
Section: Discussionmentioning
confidence: 55%
“…Besides, the global proteomic profiles of Myo-lineage cells revealed that major differences between obese-and lean-type pigs belong to categories that include muscle development, ion homeostasis, apoptosis, and the MAPK signaling pathway. In a previous study, we showed that the MAPK signaling pathway participates in the mediation of myogenic differentiation [34,35]. Thereby, in the present study, we mainly focused on the proteomic landscape among cell proliferation and differentiation, cellular ion homeostasis, and muscle development.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For pigs, cell surface marker of muscle-derived cells has not been established because of the limited knowledge of cell surface markers and available commercialized antibodies. Therefore, we had successfully established a preplate technique, a cell surface marker–-independent method, to isolate adipogenic and myogenic precursors from skeletal muscle of pigs ( 24 , 25 ) by adapting the previous protocol ( 26 ) with some modifications. In this study, we proved again the purity of adipogenic and myogenic precursors by their distinct differentiation capacity upon adipogenic and myogenic induction (as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Adipogenic and myogenic precursors were isolated from the longissimus dorsi muscle of 3-d-old newborn Yorkshire pigs according to the protocol described in our previous study ( 24 , 25 ) by adapting the previous protocol ( 26 ) with some modifications. Briefly, skeletal muscles were minced and digested in 0.17% protease (P8811; MilliporeSigma, Burlington, MA, USA) and 0.15% collagenase-type XI (C9407; MilliporeSigma) solution for 1 h, respectively.…”
Section: Methodsmentioning
confidence: 99%